LM555 timer-based inverter low power pure sinusoidal AC output - Shahid, Zeeshan; Khan, Sheroz; Alam, A. H. M. Zahirul; Ahmed, Musse Mohamud (IDOSI Publication, 2014)
The demand of highly efficient and stable DC to AC inverters used in renewable energy systems to convert DC output from green energy sources into purely sinusoidal unwavering AC is on rise, due to low cost energy generation and conversion, less complexity and environmental factors. Later this converter energy can be feed in to grid or utility supply for load sharing purpose also (can be work as Distributed Generation System (DGS)). This paper represents a duty cycle-based configuration of LM555 timer to generate an AC output of 50Hz. Two BJT transistors (NPN and PNP) are used to convert the 12V DC into 12V AC cycle. Also the low pass filter design is tested to transform distorted square wave into pure sinusoidal wave with minimum ripples on no load condition. The results shown are simulation based, showing a proper shape of 220V AC output with very less harmonics surges and noise effects